2016
DOI: 10.5267/j.msl.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Procurement risk management practices and supply chain performance among mobile phone service providers in Kenya

Abstract: The aim of this study was to establish the relationship between procurement risk management practices and supply chain performance among mobile phone service providers in Kenya. The study specifically set out to establish the extent to which mobile phone service providers have implemented procurement risk management practices and to determine the relationship between procurement risk management practices and supply chain performance. The study adopted a descriptive study design by collecting data from the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The results are supported by Okonjo, Magutu and Nyaoga (2016) who sought to establish the relationship between procurement risk management practices and supply chain performance among mobile phone service providers in Kenya. It was also clear that there was a very significant relationship between procurement risk management practices and supply chain performance represented by adjusted R 2 value of 0.646 which translates to 64.6%variance explained by the ten independent practices of Procurement Risk Management.…”
Section: Ho1: Supplier Risk Management Practices Do Not Significantly...mentioning
confidence: 66%
“…The results are supported by Okonjo, Magutu and Nyaoga (2016) who sought to establish the relationship between procurement risk management practices and supply chain performance among mobile phone service providers in Kenya. It was also clear that there was a very significant relationship between procurement risk management practices and supply chain performance represented by adjusted R 2 value of 0.646 which translates to 64.6%variance explained by the ten independent practices of Procurement Risk Management.…”
Section: Ho1: Supplier Risk Management Practices Do Not Significantly...mentioning
confidence: 66%
“…It was determined that supply chain risks have an impact on organizational performance and recommended that organizations be aware of the risks in their supply chains, assess those risks, and put contingency plans in place to deal with the ones that are most serious. Okonjo et al (2016) investigated the relationship between procurement risk management strategies and SCP among Kenyan mobile phone service providers. This research employed a descriptive approach.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…A study conducted by Okonjo (2014) on supply chain risk management in power supply industry revealed that the power sector firms are already implementing supply chain risk management practices. The study established that the power sector firms have suffered supply chain disruptions, especially the ones associated with stock outages.…”
Section: Background Of the Studymentioning
confidence: 99%